Variants in USP48 encoding ubiquitin hydrolase are associated with autosomal dominant non-syndromic hereditary hearing loss. Issue 19 (31st May 2021) - Bassani, Sissy; van Beelen, Edward; Rossel, Mireille; Voisin, Norine; Morgan, Anna; Arribat, Yoan; Chatron, Nicolas; Chrast, Jacqueline; Cocca, Massimiliano; Delprat, Benjamin; Faletra, Flavio; Giannuzzi, Giuliana; et al.
Abstract: Non-Syndromic Hereditary Hearing Loss (NSHHL) is a genetically heterogeneous sensory disorder with about 120 genes already associated. Through exome sequencing (ES) and data aggregation, we identified a family with six affected individuals and one unrelated NSHHL patient with predicted-to-be deleterious missense variants in USP48 . We also uncovered an eighth patient presenting unilateral cochlear nerve aplasia and a de novo splice variant in the same gene. USP48 encodes a ubiquitin carboxyl-terminal hydrolase under evolutionary constraint. Pathogenicity of the variants is supported by in vitro assays that showed that the mutated proteins are unable to hydrolyze tetra-ubiquitin. Correspondingly, three-dimensional representation of the protein containing the familial missense variant is situated in a loop that might influence the binding to ubiquitin . Consistent with a contribution of USP48 to auditory function, immunohistology showed that the encoded protein is expressed in the developing human inner ear, specifically in the spiral ganglion neurons, outer sulcus, interdental cells of the spiral limbus, stria vascularis, Reissner's membrane and in the transient Kolliker's organ that is essential for auditory development. Engineered zebrafish knocked-down for usp48, the USP48 ortholog, presented with a delayed development of primary motor neurons, less developed statoacoustic neurons innervating the ears, decreased swimming velocity and circling swimming behavior indicative of vestibular dysfunction and hearing impairment. Corroboratingly, acoustic startle response assays revealed a significant decrease of auditory response of zebrafish lacking usp48 at 600 and 800 Hz wavelengths. In conclusion, we describe a novel autosomal dominant NSHHL gene through a multipronged approach combining ES, animal modeling, immunohistology and molecular assays.